2021
DOI: 10.1002/jor.25233
|View full text |Cite
|
Sign up to set email alerts
|

Structural and pathological changes in the enthesis are influenced by the muscle contraction type during exercise

Abstract: Mechanical stress is involved in the onset of sports‐related enthesopathy. Although the amount of exercise undertaken is a recognized problem during disease onset, changes in muscle contraction type are also involved in the increase in mechanical stress during exercise. This study aimed to clarify the effects of increased mechanical stress associated with muscle contraction type and amount of exercise on enthesis. Twenty mice underwent treadmill exercise, and the muscle contraction type and overall load during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Furthermore, our previous study showed that the UFC increased at a higher rate than the CFC. 10 Therefore, the early stage of sports-related enthesopathy-like morphological changes may have been caused by the activation of molecular pathways through the tendon, in addition to the effects of EC-specific mechanical stress on the FC region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, our previous study showed that the UFC increased at a higher rate than the CFC. 10 Therefore, the early stage of sports-related enthesopathy-like morphological changes may have been caused by the activation of molecular pathways through the tendon, in addition to the effects of EC-specific mechanical stress on the FC region.…”
Section: Discussionmentioning
confidence: 99%
“…The tendon CSA was measured in the thinnest region of the tendon. The FC and SB regions just below the enthesis FC region were analyzed based on our previous experiments 10 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations